2011
DOI: 10.1101/gad.633311
|View full text |Cite
|
Sign up to set email alerts
|

The inactive X chromosome adopts a unique three-dimensional conformation that is dependent on Xist RNA

Abstract: Three-dimensional topology of DNA in the cell nucleus provides a level of transcription regulation beyond the sequence of the linear DNA. To study the relationship between the transcriptional activity and the spatial environment of a gene, we used allele-specific chromosome conformation capture-on-chip (4C) technology to produce high-resolution topology maps of the active and inactive X chromosomes in female cells. We found that loci on the active X form multiple long-range interactions, with spatial segregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
306
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 288 publications
(340 citation statements)
references
References 62 publications
16
306
2
1
Order By: Relevance
“…Distances were measured manually from the center of each BAC signal to the edge of the closest chromocenter (marked by satellite probe) using ImageJ software as previously described (Splinter et al 2011). Association was called when distances between the center of the BAC signal and the edge of the closest chromocenter were <0.3 μm, the maximum distance at which visual associations (touching signals) have been observed in our measurements.…”
Section: Image Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Distances were measured manually from the center of each BAC signal to the edge of the closest chromocenter (marked by satellite probe) using ImageJ software as previously described (Splinter et al 2011). Association was called when distances between the center of the BAC signal and the edge of the closest chromocenter were <0.3 μm, the maximum distance at which visual associations (touching signals) have been observed in our measurements.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…For probe labeling, the lacO transgene and a bacterial artificial chromosome (BAC) across the Llgl2 locus (RP23-143F14) were fragmented with Sau3A, while major satellite repeats were PCR-amplified from diluted genomic DNA to obtain fragments corresponding to 1-3 repeats. Probes were labeled as previously described (Splinter et al 2011) with the BAC, lacO transgene, and satellites labeled in green, Cy3 and Cy5, respectively (Cat. #42845, 42501, and 42502, Enzo Life Sciences).…”
Section: Dna Fluorescent In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For a better understanding of histone modifications and chromatin, a number of excellent reviews (Grimaud et al, 2006;Ringrose and Paro, 2004;Schuettengruber et al, 2007) focus on these subjects. Moreover, Pc complexes contribute crucially during embryogenesis, tissue differentiation (Pietersen and van Lohuizen, 2008;Sparmann and van Lohuizen, 2006) and tumorigenesis (Schlesinger et al, 2007;Widschwendter et al, 2007) through X-chromosome inactivation (Casanova et al, 2011;Splinter et al, 2011) and regulation of imprinted genes ( Jullien et al, 2006;Makarevich et al, 2006;Schubert et al, 2006). Pc complexes are also associated with nuclear reprogramming and chromatin remodeling (for a review, see Golbabapour et al, 2011).…”
Section: Polycomb Complexes and Their Biological Rolesmentioning
confidence: 99%
“…Xist spreads along the entire X chromosome and represses transcription by multiple mechanisms. 28 Xist binding changes the chromatin conformation of the X chromosome 29 and its spreading depends on the 3D organization of the X chromosome. Chromosome Conformation Capture techniques demonstrated that the first regions bound by Xist are in close proximity to the Xist locus in the nuclear space.…”
Section: A Nuclear Organizationmentioning
confidence: 99%